2023
DOI: 10.1039/d2mh00998f
|View full text |Cite
|
Sign up to set email alerts
|

A processable, scalable, and stable full-color ultralong afterglow system based on heteroatom-free hydrocarbon doped polymers

Abstract: Although the room-temperature phosphorescence (RTP) organic material is a long-studied topic and has become especially popular in the recent decade, all-round players with qualified long-lived RTP lifetimes to fulfill the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 94 publications
0
40
0
Order By: Relevance
“…Ultralong organic room-temperature phosphorescence (UORTP) has been attracting considerable attention in past years due to its superiorities of low toxicity and flexible structural modification and its wide applications in bioimaging/sensing, encryption/anticounterfeiting, , organic light-emitting diodes, etc. 1 H -Benzo­[ f ]­indole (Bd), a type of carbazole isomer, has been recognized as an important building block for UORTP materials since Prof. Bin Liu refined it from commercial carbazole.…”
Section: Introductionmentioning
confidence: 99%
“…Ultralong organic room-temperature phosphorescence (UORTP) has been attracting considerable attention in past years due to its superiorities of low toxicity and flexible structural modification and its wide applications in bioimaging/sensing, encryption/anticounterfeiting, , organic light-emitting diodes, etc. 1 H -Benzo­[ f ]­indole (Bd), a type of carbazole isomer, has been recognized as an important building block for UORTP materials since Prof. Bin Liu refined it from commercial carbazole.…”
Section: Introductionmentioning
confidence: 99%
“…On account of the excellent mechanical flexibility and large-area producibility, this polymer-related phosphorescent system had a bright opportunity for the construction of complex 3D objects with afterglow, curling, and repeatable folding properties (Figure c, inset). More interestingly, Zheng et al recently confirmed that pure polycyclic aromatic hydrocarbons may outperform phosphorescent chromophores containing heteroatoms or heavy atoms (Figure d). With the increasing conjugation extent of chromophores, full-color (blue, green and orange) phosphorescence can be measured in polymeric systems.…”
Section: Synthesis Strategies Of Room-temperature Phosphorescence In ...mentioning
confidence: 89%
“…(e) Flexible 3D objects with high-intensity phosphorescence. Reprinted with permission from ref . Copyright 2023 Royal Society of Chemistry.…”
Section: Synthesis Strategies Of Room-temperature Phosphorescence In ...mentioning
confidence: 99%
“…In previous studies, coronene was incorporated into host materials with high oxygen barrier properties, such as β ‐estradiol [11] and poly(methyl methacrylate), [12] and the organic RTP materials with long phosphorescence lifetimes of 17 s (deuterated coronene) [8] and 6 s [9] in air, respectively, were reported. However, in these host materials (organic small molecules [6,8,13] and polymers [6–7,9,14] ), the aggregation of guest molecules, [15] low solubility of guest molecules to host materials during incorporation, [7a] and aggregation of guest molecules over time [7b] remain problematic.…”
Section: Introductionmentioning
confidence: 99%